2-Aroylindoles from o-bromochalcones via Cu(I)-catalyzed SNAr with an azide and intramolecular nitrene C-H insertion - Goriya, Yogesh; Ramana, Chepuri V. (Chemical Communications, 2014)
A simple procedure for the synthesis of 2-aroylindole derivatives comprising a one-pot CuI-catalyzed SNAr reaction of o-bromochalconeswith sodium azide and subsequent intramolecular cyclization through nitrene C-H insertion has been developed. This protocol is also applicablewith the 2'-bromocinnamates giving the indole-2-carboxylates.